Syntheses, Antibacterial, Cytotoxic and Antifungal Effects of New 3-Carboxy-1-phenacylpyridinium Salts - Khan, Khalid Mohammed; Saify, Zafar Saeed; Shah, Syed Tasadaque Ali; Ahmed, Mansoor; Saeed, Muhammad; Hayat, Safdar; Abbas, Muhammad; Voelter, Wolfgang (Arzneimittelforschung, 2002)
Thirteen pyridlne-3-carboxylic acid salt derivatives with various substituted phen-acyl residues were prepared and their cytotoxicity, antibacterial and antifungal activities tested. Compounds 5 and 11 proved to be active in the brine shrimp bioassay, compounds 7, 9–12 and 14 showed promising antibacterial activities, whereas none of the compounds tested against 15 fungal cultures proved to be active. Extensive spectroscopic techniques were employed to confirm the structure of the synthetic products.
Keywords: ■ Pyridine-3-carboxylic acid derivatives, antibacterial activity, antifungal; activity, cytotoxicity, synthesis